2013
DOI: 10.1002/jms.3243
|View full text |Cite
|
Sign up to set email alerts
|

Rapid analysis of neurotransmitters in rat brain using ultra‐fast liquid chromatography and tandem mass spectrometry: application to a comparative study in normal and insomnic rats

Abstract: Neurotransmitters and their metabolites in central nervous system were known to play a significant role in sedation and hypnosis. A rapid and sensitive UFLC-MS/MS method for simultaneous determination of serotonin, 5-hydroxyindole acetic acid (5-HIAA), tryptophan (Try), dopamine (DA), norepinephrine (NE), γ-aminobutyric acid (GABA), glutamic acid (Glu) and acetylcholine (Ach) in rat brain without derivatization, ion-pairing reagent or pre-concentration was developed. Analytes and IS were separated on a Inertsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…However, even when compared with these methods, the present method obtained a notable improvement in the sensitivity. Generally, the reported LLOQs determined on matrix‐free samples were within the ranges of 0.3–2, 0.4–15, 0.4–12 and 0.4–135 ng/mL for DA, 5‐HT, 5‐HIAA and DOPAC, respectively (Gonzáles et al, ; He et al, ; Kim et al, ; Kim et al, ; Liu et al, ; Najmanová et al, ; Wojnicz et al, ). The low LLOQs of the present method made it possible to quantitate the substances at low concentrations in small sample masses, for example 2 mg of BO and 10 mg of CB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even when compared with these methods, the present method obtained a notable improvement in the sensitivity. Generally, the reported LLOQs determined on matrix‐free samples were within the ranges of 0.3–2, 0.4–15, 0.4–12 and 0.4–135 ng/mL for DA, 5‐HT, 5‐HIAA and DOPAC, respectively (Gonzáles et al, ; He et al, ; Kim et al, ; Kim et al, ; Liu et al, ; Najmanová et al, ; Wojnicz et al, ). The low LLOQs of the present method made it possible to quantitate the substances at low concentrations in small sample masses, for example 2 mg of BO and 10 mg of CB.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, LC coupled to a tandem mass spectrometer (MS/MS) via an electrospray ionization (ESI) interface has been introduced for NT analyses, mainly owing to the higher selectivity of this technique. Generally, the LC–ESI–MS/MS methods published so far for brain analysis use simple extraction procedures without further sample clean‐up before injection onto the analytical column (Fuertig et al, ; Gonzáles, Fernández, Vidal, Frenich, & Pérez, ; He et al, ; Huang et al, ; Kim, Choi, Kim, & Kim, ; Kim, Kim, Hong, & Kim, ; Liu et al, ; Marcos et al, ; Najmanová et al, ; Tareke, Bowyer, & Doerge, ; Wojnicz et al, ; Xu et al, ; Zheng et al, ). The crude extract, which is often pre‐concentrated using solvent evaporation, contains matrix components that may affect the accuracy of the results and compromise the lower limit of quantification (LLOQ) owing to interferences and ion suppression in the ESI interface (Peters, Drummer, & Musshoff, ; Srinivas, ; van Eeckhaut, Lanckmans, Sarre, Smolders, & Michotte, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, many methods have been developed to detect Glu and these related amino acids in brain tissues, such as gas chromatography with mass spectrometry (Pinto et al ., ; Wood et al ., ; Kapetanovic et al ., ), liquid chromatography with ultra‐violet detection (Wu et al ., ; Kang et al ., ) and liquid chromatography combined with electrochemical detection (Murai et al ., ; Monge‐Acuña and Fornaguera‐Trías, ). Among these methods, liquid chromatography combined with tandem mass spectrometry (LC‐MS/MS) is the most frequently used method for the simultaneous determination of Glu analogs in brain tissues (Kim et al ., ; Huang et al ., ; Wei et al ., ; He et al ., ). However, when using an LC‐MS/MS protocol for the accurate quantification of Glu analogs, Purwaha et al () reported that free Glu and glutamine (Gln) are cyclized to pyroglutamic acid (pGlu) in the electrospray ionization (ESI) source (Fig.…”
Section: Introductionmentioning
confidence: 97%
“…Various biophysical methods have been used to identify and quantify the biochemical composition of synaptosomes to better understand its potential relationship to psychiatric and neurodevelopmental illness. Mass spectrometry (MS) is widely used to analyze the synaptosome and to identify the proteins and neurotransmitters involved in neuropsychiatric disorders [28][29][30][31]. However, MS has several disadvantages that limit its ability to accurately identify and quantify neurotransmitters in synaptosomes, including matrix interference, consistency and reproducibility in sample preparation, matrix inhomogeneity, and low mass resolution and spatial resolution of instruments [32].…”
Section: Introductionmentioning
confidence: 99%